The ability of subsurface dams to protect freshwater abstraction wells against seawater intrusion in heterogeneous aquifers - Antoifi Abdoulhalik; Ismail Abd-Elaty; Ashraf A. Ahmed (Cleaner Water)
The main purpose of this study was to examine the ability of subsurface dams to protect freshwater abstraction against seawater intrusion in both homogeneous and layered aquifers. Laboratory experiments were conducted in a synthetic aquifer where a subsurface dam was simulated in a homogeneous scenario (case H), and in another scenario where a top low-permeability (low-K) layer was placed in the upper part of the aquifer (case LH). We then conducted numerical simulations using the SEAWAT model to validate the experimental results. We also examined other numerical cases where a low-K layer existed at the middle (case HLH) and the bottom of the aquifer (case HL). The existence of a low-K layer has generally delayed the upconing, and it took longer for the SWI to contaminate the abstraction well. The top low-K layer case needed 52 % more pumping than the homogeneous aquifer for the wedge to spill over the dam into the landward side. The clean-up time varied substantially from one case to another, with the case HL taking longer than the other cases for SWI removal. The cleanup time was reduced by 23 % in the presence of a top low-K layer compared to the homogeneous aquifer. The study demonstrates that a low-K layer on the top of the aquifer contributed positively to improving the ability of the subsurface dams to obstruct SWI, limit saltwater upconing and, therefore, allow more optimal freshwater abstraction. A feature of this study was that it examined the ability of dams to prevent seawater intrusion in the presence of freshwater pumping, which has not been investigated in previous studies, at least in laboratory experiments.